Learning in lockdown: exploring the impact of COVID-19 on interprofessional education. (2nd November 2021) - Power, Alison; Palapal Sy, Michael; Hutchings, Maggie; Coleman, Tracy; El-Awaisi, Alla; Kitema, Gatera Fiston; Gallagher, Jean; Herath, Chulani; McLarnon, Nichola; Nagraj, Shobhana; O'Carroll, Veronica; Owens, Melissa; et al.
Abstract : The COVID-19 pandemic has had a significant impact on the learning experiences of students undertaking health and social care programmes across the globe. In the UK, the Nursing and Midwifery Council introduced emergency standards for undergraduate programmes in 2020, making significant short-term changes to programme delivery. However, the mandate for all students to undertake interprofessional education remained. Interprofessional education is key to preparing students on health and social care programmes, as it enables students to work as effective members of multi-agency/multi-professional teams on qualification. It is an important element of training, as it has a direct impact on quality of care and service user experience. This series of articles will explore the experiences of 'lockdown learning' from the perspective of academics, students and service users from a global perspective in relation to the delivery of interprofessional education during the pandemic, which necessitated a wholesale move from face-to-face, blended and online learning to include emergency remote teaching. The series was written by members of the Centre for the Advancement of Interprofessional Education Research Subgroup (Interprofessional Education Experiences) and aims to identify barriers and facilitators to successful shared learning and provide suggestions for how lessons learned can be taken forward to further enhance this important element of pre-registration education. The perceptions and attitudes of academics and students on such comprehensive changes are a unique and rich data source to explore and inform future provision.